2009 IEEE International Technology Management Conference (ICE) 2009
DOI: 10.1109/itmc.2009.7461378
|View full text |Cite
|
Sign up to set email alerts
|

A web-based platform for collaborative product design and evaluation

Abstract: This paper presents a web-based integrated platform for supporting the collaborative product design activities. An overview of the overall Digital Factory framework, in which the Collaborative Prototype Designer (CPD) resides, has been given flrst. Next, the CPD's functional architecture is presented including the way it addresses the needs for collaboration during the product design process. The CPD is based on the integration of a spectrum of technologies, including Content Management, Computer-Aided Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…It is moreover increasingly easier to implement and use thanks to unceasing progress in dedicated hardware and software. Virtual reality is used in several activities in industry: product or process design (Berg & Vance, 2017;Smparounis et al, 2009), facility layout (Menck et al, 2012), training (Marzano, Friel, Erkoyuncu, & Court, 2015), or remote collaboration (Galambos et al, 2015). Virtual reality helps to do right first time and involves stakeholders in the decision process (Gong, Berglund, Saluäär, & Johansson, 2017).…”
Section: Virtual Realitymentioning
confidence: 99%
“…It is moreover increasingly easier to implement and use thanks to unceasing progress in dedicated hardware and software. Virtual reality is used in several activities in industry: product or process design (Berg & Vance, 2017;Smparounis et al, 2009), facility layout (Menck et al, 2012), training (Marzano, Friel, Erkoyuncu, & Court, 2015), or remote collaboration (Galambos et al, 2015). Virtual reality helps to do right first time and involves stakeholders in the decision process (Gong, Berglund, Saluäär, & Johansson, 2017).…”
Section: Virtual Realitymentioning
confidence: 99%
“…For example, DiFac [Sacco et al 2007] showed how the design of industrial production sites benefits from virtual design and evaluation. Smparounis et al [Smparounis et al 2009] presented a browser-based solution of a collaborative prototype designer. Zinnikus et.…”
Section: Collaborative Content Creationmentioning
confidence: 99%
“…In order to facilitate these members, design techniques which easily represent a product concept or component for design evaluation must be utilised. AR technologies have been implemented extensively for collaborative design applications [12][13][14][15][16] allowing for representation, evaluation and modification of a design in a group environment.…”
Section: Collaborative Designmentioning
confidence: 99%